Approaches to the creation of information and analytical system for evaluation of efficiency of mathematical models (Computer systems and information technologies, 2020)
The article is devoted to the substantiation of the choice of the basic technique of estimation of efficiency of mathematical models which could be accepted as the basic model at the development of the corresponding information-analytical system, and also the definition of those provisions which need to be considered in the specified basic technique. The study found that as a basic method of evaluating the effectiveness of mathematical models, it is advisable to adopt a methodologybased on a combination of existing approaches to evaluating efficiency, the first of which concerns the implementation of stages of evaluating the feasibility of modeling, comparative evaluation of models, the second is the quantitative assessment of significant requirements for mathematical models of phenomena, processes, and systems. These approaches should complement each other at the macro and micro levels by implementing the properties of additivity and superposition of important provisions for modeling, which are different in different approaches. In this case, the main aspects that determine the necessary areas for improvement of the basic methodology are aspects related to the creation of instrumental methods for estimating the speed and material costs of creating a model and evaluating the research result obtained using modeling, as well as substantiation of analytical dependencies. to determine the average criterion assessment of the model, integrated assessment of incremental effects, reliability of modeling, relative average values of error introduced into model calculations due to generalized consideration of parameters and factors, dependence for absolute assessment of modeling completeness.
Keywords: information-analytical system; efficiency; mathematical model; methodology; evaluation; indicators; factors; dependence; approaches